The use of SME tax incentives in the European Union - Sören Martin Bergner; Rainer Bräutigam; Maria Theresia Evers; Christoph Spengel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
This paper discusses the impact and the appropriateness of tax incentives for small and medium-sized enterprises (SMEs) in the European Union. First, we provide a survey of implemented tax incentives specifically targeted at SMEs in the 28 EU Member States. Building hereon, we measure the impact of these regimes on the effective tax burdens of targeted companies. We find that SME tax incentives are a commonly used measure among European policy makers. The vast majority of regimes, however, only marginally reduce the tax liability of SMEs. If major reliefs are available, they mostly stem from special tax rates whereas tax credits and special allowance play a minor role. In the second main part of the analysis, we examine the arguments potentially justifying the usage of SME tax incentives. As a main result, small firms per se do not create more jobs and innovations nor do they face insurmountable financing constraints. The existence of market failures commonly associated with SMEs - and possibly warranting the use of SME tax incentives - can therefore not be confirmed. Instead, disproportionate tax compliance costs for small entities constitute the most compelling argument for a special tax treatment. These compliance costs can most appropriately be addressed by administrative reliefs. Special tax rates, tax credits and allowances, in contrast, are not only inefficient but also ineffective in this regard. Instead of improving the neutrality of the overall tax system, the latter are likely to add further distortions and unnecessary complexity. Altogether, the focus of policy-makers should thus shift from providing discriminatory incentives to the design of a generally neutral and simple tax system, which would benefit small as well as large enterprises.
urn:nbn:de:bsz:180-madoc-419753
Keywords: H24; H25; 330; SME; Tax Policy; European Union